Pemanfaatan Limbah Padat Bulu Ayam pada Usaha Home Industry Rumah Pemotongan Ayam menjadi Kerajinan Tangan - Fachrezi, Rizki Rahman; Waskito, Zaid Tegar; Ramadhan, Muhammad Rizki; Hidayatulloh, Rendy Tri; Wijaya, Jaya (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
This observation aims to determine the waste in the slaughterhouse and utilize solid waste into handicrafts. In this broiler business, the concept of environmental efficiency has not been fully implemented. There is still a lot of waste that is thrown away without thinking about the impact it will have. Waste that is not recycled again will have an impact on water, air and soil pollution. The waste found in the poultry business includes water waste and solid waste. Waste generated from wastewater is water from washing chickens. Meanwhile, the solid waste produced is dead poultry, chicken internal organs, chicken feathers thrown into the river, and chicken manure. The implementation in this observation is by conducting a literature study, conducting direct observations, taking samples or materials to be processed, educating owners and employees, processing or recycling solid waste that will be recycled into handicrafts. There must be awareness from business actors and employees to apply the principles of green manufacturing and the importance of health and the impact it has on the surrounding community and implement a recycling process on solid waste found or utilize effective process technology that allows the production of raw materials for other sectors while reducing amount of waste generated.